Desenvolvimento dos órgãos linfoides de larvas de pacu (Piaractus mesopotamicus) em resposta a diferentes manejos alimentares - Elias, Amanda Halum [UNESP] (2015)
The development of the lymphoid organs in pacu larvae (Piaractus mesopotamicus) since hatching until 34 days of age and the effects of different feeding protocols on the morphogenesis of the immune system and the resistance of ar exposure were investigated. The feeding treatments studied were: (TP) early weaning, replacement of artêmia nauplii by commercial microdiet initiated at eight days after the first feeding; (TT) late weaning, replacement initiated at 15 after the first feeding; (ART) larvae fed exclusively artemia nauplii. The histological samples to describe the ontogeny of the kidney, thymus and spleen were taken twice a day until 13 days pos-hatch (dph), once a day until 16 dph and then each three days until the end of the experiment. On the first feeding day, 7, 11, 16, 22 and 30 days after the beginning of the active feeding, biometrics were made. A stress resistance test (air exposure for 1, 3, 5, 7 e 20 min) was applied to the larvae 12 days after the end of the early and late weaning, respectively, after 22 and 29 days of feeding. The histogenesis of the lymphoid organs demonstrated that the fisrt organ to became lymphoid was the thymus with 2 dph, although the kidney had been observed since the moment the larvae hatched. At 6 dph, the kidney show signs of differentiation. The spleen was the last organs to appear at 6 dph. At 35 dph the kidney had already differentiated into head kidney (with monocytes, lymphocytes and hematopoietic tissue) and posterior kidney (renal tubules). The thymic parenchyma didn't present differences, however the cells differentiated in the inner and outer zones and the spleen did not present differentiation between red and white pulp until this period. Comparing to the treatment that received only artemia nauplii, early and late weaning reduced de survival of the larvae. However, only the early weaning decreased the specific growth rate and weight gain and caused difference on larvae size ...